A Comparative Study On Characteristic And Antimicrobial Activity Of Cinnamon (C. Zeylanicum) Oil Small-Sized Emulsion By Phase Inversion Composition And Phase Inversion Temperature Methods. - Roslan, Rohardiyana; Mansur, Sity Aishah; A Talip, Balkis (Progress in Engineering Application and Technology, 2020)
Cinnamomum zeylanicum (C. zeylanicum) is species of cinnamon, which a native plant to Sri Lanka, India and Madagascar that consist of a variety of biologically active compounds that makes C. zeylanicum able to act as an antimicrobial agent against both Gram-negative and Gram-positive bacteria. The ability of C. zeylanicum to act as antimicrobial agent could make it as a natural preservative in food products. However, the cinnamon oil that extracted from C. zeylanicum is in a lipophilic compound which are insoluble in water and hard to be applied directly to the food products as preservatives. These problems may be overcome by formulating essential oils into small-sized emulsions to increase solubility and stability of droplets. This study will help to produce small-sized emulsions from cinnamon oil as natural preservative in food products by using phase inversion composition (PIC) and phase inversion temperature (PIT) methods. Different formulation ratios between cinnamon essential oil to grape seed carrier oil were used. The antibacterial activity of small-sized emulsions was evaluated using minimum inhibitory concentration (MIC) and minimum inhibitory zone (MIZ) assays against Bacillus cereus (B. cereus), Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). Small-sized emulsions produced by PIT are smaller than small-sized emulsions by PIC with 2.84 μm average droplet size. All sample mixtures of cinnamon oil with grape seed oil were found to be more acidic in the range of 4.23 to 4.78. Turbidity of small-sized emulsions produced by PIT method have a lower absorbance value than small-sized emulsions produced by PIC which could promote a better stability of emulsions. The antibacterial study found that all sample mixture small-sized emulsions of cinnamon oil able to inhibit B. cereus, E. coli and S. aureus at minimum concentration 12.5%, 6.25% and 12.5% respectively. Development of inhibition zone against B. cereus, E. coli and S. aureus were found with 0.70 cm, 0.95 cm and 0.80 cm respectively. Therefore, application of high concentration of surfactant and high temperature does give impact to the size and uniformity of emulsions and its ability in inhibit bacteria. The small-sized emulsions produced by PIC and PIT methods of cinnamon oil with combination grape seed oil is proven to be an alternative treatment with antibacterial activity and also can act as an antibacterial agent in preservation of foods.